Retrograde plastid redox signals in the expression of nuclear genes for chloroplast proteins of Arabidopsis thaliana - Fey, Vidal; Wirtz, Markus; Hell, Rüdiger (The journal of biological chemistry, 2005)
Excitation imbalances between photosystem I and II generate redox signals in the thylakoid membrane of higher plants which induce acclimatory changes in the structure of the photosynthetic apparatus. They affect the accumulation of reaction center and light-harvesting proteins as well as chlorophylls a and b. In Arabidopsis thaliana the re-adjustment of photosystem stoichiometry is mainly mediated by changes in the number of photosystem I complexes, which are accompanied by corresponding changes in transcripts for plastid reaction center genes. Because chloroplast protein complexes contain also many nuclear encoded components we analyzed the impact of such photosynthetic redox signals on nuclear genes. Light shift experiments combined with application of the electron transport inhibitor 3-(3′,4′-dichlorophenyl)-1,1′-dimethyl urea have been performed to induce defined redox signals in the thylakoid membrane. Using DNA macroarrays we assessed the impact of such redox signals on the expression of nuclear genes for chloroplast proteins. In addition, studies on mutants with lesions in cytosolic photoreceptors or in chloroplast-to-nucleus communication indicate that the defective components in the mutants are not essential for the perception and/or transduction of light-induced redox signals. A stable redox state of glutathione suggest that neither glutathione itself nor reactive oxygen species are involved in the observed regulation events pointing to the thylakoid membrane as the main origin of the regulatory pathways. Our data indicate a distinct role of photosynthetic redox signals in the cellular network regulating plant gene expression. These redox signals appear to act independently and/or above of cytosolic photoreceptor or known chloroplast-to-nucleus communication avenues.